Total Antioxidant Status in Critically Ill Patients with Traumatic Brain Injury and Secondary Organ Failure—A Systematic Review - Ewa Rynkiewicz-Szczepanska; Urszula Kosciuczuk; Mateusz Maciejczyk (Diagnostics)
Introduction: The available literature indicates that oxidant–antioxidant imbalance plays a significant role in the pathophysiology of traumatic brain injury and the subsequent secondary organ dysfunctions. However, there is a lack of studies summarizing the knowledge in this area, and no clear guidelines exist regarding the use of biomarkers of oxidative stress as diagnostics tools. Methods: The present work aims to provide a systematic review of the literature on the use of total antioxidant capacity (TAC) assays in predicting the outcomes of traumatic brain injury (TBI). A literature search was conducted up to 1 September 2024, according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) guidelines, using the PubMed and Scopus databases. Based on the inclusion criteria, 24 studies were used for the final review. Results: Promising data indicate that TAC assays are useful in predicting 30-day mortality and neurological outcomes. Moreover, they correlate with radiological findings on CT scans in brain injury and the clinical classifications of injuries, as well as the parameters of organ failure. Conclusions: Total antioxidant capacity assays can be used to assess the extent of brain damage and prognosticate general vital functions. Future experiments should include long-term randomized clinical trials on larger populations of TBI patients.